Mobile and Ubiquitous Commerce 2009
DOI: 10.4018/978-1-60566-366-1.ch005
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Adoption of Mobile Government Services

Abstract: Mobile government transform many of the traditional governance practices. The citizens’ adoption of M-Government services (e.g. voting, tax services, health services, etc.), however, is determined by a series of factors (e.g. ease of use, image, compatibility, etc.). This chapter investigates the predicting power of these factors towards contributing to theory building and providing direct implications that are useful for the diffusion and adoption of mobile government services in Greece. The study reviews the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In a study [6] that has been carried out to investigate factors relevant to diffusion and adoption of M-Government in Greece, findings revealed that ease of use and compatibility could affect the adoption behavior. Another study [7] has been conducted to determine issues surrounding M-government services adoption in Jordon, results showed that public awareness, infrastructural limitations and lack of comprehensive legal framework were among the critical issues surrounding the use of M-government.…”
Section: Similar Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study [6] that has been carried out to investigate factors relevant to diffusion and adoption of M-Government in Greece, findings revealed that ease of use and compatibility could affect the adoption behavior. Another study [7] has been conducted to determine issues surrounding M-government services adoption in Jordon, results showed that public awareness, infrastructural limitations and lack of comprehensive legal framework were among the critical issues surrounding the use of M-government.…”
Section: Similar Workmentioning
confidence: 99%
“…The advancement in wireless communication has paved the way to the emergence of M-government. M-government can be seen as an effective and efficient solution for delivering services using mobile technology [2][3][4][5][6][7][8][9][10][11][12][13]. The goals and objectives of M-government are diverse including -but not limited to-saving time, cost and effort through providing efficient services to citizens using electronic channels [14].…”
Section: Theory Backgroundmentioning
confidence: 99%
“…According to Karadimas & Papantoniou (2008) and Ntaliani et al (2008) m-government in Greece is still in its infancy and they propose some additional future m-services that could improve the governmental organization and citizens' satisfaction; such services are mobile transport ticketing, m-parking and sending time critical notifications. Vrechopoulos (2009), finally, writes about factors predicting the m-services adoption by the Greek citizens.…”
Section: Proposed Typology Of Mobile G2c Servicesmentioning
confidence: 99%